ISU E-BUDAYA DALAM EVALUASI PROGRAM PENDIDIKAN PADA SEKOLAH DASAR - Widialistuti, Refny; Ambiyar, Ambiyar; Aziz, Ishak (Cerdas Proklamator, 2022)
This study aims to describe the issue of E-Culture contained in the Minister of Education and Culture Number 54 of 2016. E-Culture in question is the development of learning media that has cultural elements. The development has been carried out since 2015 and has yet to go through the evaluation stage. This study used literature studies obtained from the results of reviews in several journals. The results of the study are categorized to analyze the development of E-Culture in evaluating educational programs at elementary school. The results show that the E-cultural element needs to be developed to adapt the application of the 2013 curriculum in learning so that the assessment application in the grade increase exam can combine the material following the content in the learning process.